MANAJEMEN PENGAMBILAN KEPUTUSAN DALAM ORGANISASI PENDIDIKAN - Dr. Yayah Huliatunisa; Nurlaelah Nurlaelah; Indah Rahmatul Hasanah (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
Decision making is a human cognitive process that results in the selection of beliefs or actions among several alternatives options either rationally or irrationally. In an educational organization decision making plays a key role in terms of motivation, leadership, communication, coordination, and organizational change. An organization only work if its leaders have the ability to make decisions and its implemation to its members as determined by their roles and responsibilities. By using literary techniques, this study confirms that decision making of an educational organization must realize several basic principles, namely authority, credibilty, reference, ethics, orientation, and scope. Based on this principle, decisions are made using one of the classical, administrative, incremental, administrative-incremental, and contingecy paradigms.